Síntese e caracterização de nanocristais semicondutores magnéticos diluídos de Pb1-xCoxS em matrizes vítreas - MELO, Roney Eustáquio Silva (2018)
The present study synthesized and characterized PbS and Pb1-xCoxS nanocrystals in vitreous matrices of chemical composition defined by 40SiO2.30Na2CO3.1Al2O3.25B2O3.4PbO2 (mol%). In view of this, fusion-nucleation and heat treatment methods were used at temperatures of 500ºC. In order to confirm the formation of the nanocrystals, the researcher applied some techniques of experimental analysis, such as Differential Thermal Analysis (DTA), Atomic Force Microscopy (MFA)/Magnetic Force Microscopy (MFM), X-Ray Diffraction (DRX), Transmission Electron Microscopy (MET)/Dispersion Energy Spectroscopy (EDS) and Optical Absorption Spectroscopy UV-VIS-NIR (Ultraviolet-VisibleNear infra-red). In the crystalline structure of PbS, X-ray diffraction peaks were observed to the right, which evidenced the insertion of Co2+ ions. MET and MFM provided results using topographic and EDS graphs that confirmed the growth of PbS and Pb1-xCoxS nanocrystals with quantum dot formation and magnetization in the SNABP SiO2.Na2CO3.Al2O3.B2O3.PbO2 chemical composition glass matrix. With the aid of the UV-VIS-NIR Optical Absorption Spectroscopy technique, the growth of the nanocrystals and the displacement of the peaks at higher wavelengths were evaluated as a function of the thermal treatment, at a temperature of 500ºC, for different time intervals of heat treatment. The crystalline field theory, together with Tanabe-Sugano diagram, provided answers that evidence the incorporation of Co2+ ions into tetrahedral sites of the PbS crystal structure.